PENGARUH BAHAN AJAR MATEMATIKA BERKARAKTER PADA MATERI TURUNAN FUNGSI TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN DISPOSISI MATEMATIKA SISWA SMA: Studi eksperimen terhadap siswa kelas XI SMA Negeri 4 Bandung - Riyanti, Reni (2013)
This research was back grounded by the low ability of students' mathematical problem solving and the character values which are not correspond to the purpose of education. In addition, one of the factors supporting the success of students learning math is math disposition. The purpose of this research is: 1) examines the mathematics characterized learning materials model; 2) analyzing the improvement of problem solving ability on mathematics characterized learning materials with the common learning materials; 3) analyze the differences of mathematics disposition in mathematics characterized learning materials the common learning materials. The method used in this research is the kual-kuan, mixed qualitative and quantitative models. The design on this research is control group pre test - post test. The subjects in this study were students of Class XI IPA 4and XI IPA 6 SMA Negeri 4 Bandung. This study was conducted in two stages, stage 1 is identification of learning obstacle and stage 2 is the experiments testing of the effects of mathematics characterized learning materials toward the mathematical problem solving ability. The instruments used in this research were a test, disposition questionnaire, and observation guidelines. Learning obstacles identified were the students' ability in identifying problems and devising mathematical models, as well as the relation between mathematical concepts and the relation of Mathematics with other disciplines. The conclusions drawn in this study is a model of learning materials used is customized with the students' learning obstacle, the improvement of students' mathematical problem solving ability using mathematics characterized learning material was better than the students who learn using a common learning materials, and the mathematics disposition of students who learn through mathematics characterized learning materials was better than the students who learn using a common learning materials. Key Words: mathematics characterized learning material, mathematical problem solving, mathematics disposition Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemecahan masalah matematis siswa dan nilai karakter yang tidak sesuai dengan tujuan pendidikan. Selain itu, salah satu faktor penunjang keberhasilan belajar matematika siswa adalah disposisi matematika. Tujuan penelitian ini adalah: 1) mengkaji model bahan ajar matematika berkarakter; 2) menganalisis peningkatan kemampuan pemecahan masalah pada bahan ajar matematika berkarakter dengan bahan ajar biasa; 3) Menganalisis perbedaan disposisi matematika pada bahan ajar matematika berkarakter dengan bahan ajar biasa. Metode yang digunakan dalam penelitian ini adalah kual-kuan yang merupakan model campuran kualitatif dengan kuantitatif. Desain pada penelitian ini adalah control group pre-test-post-tes. Yang menjadi subjek dalam penelitian ini adalah siswa kelas XI IPA 4 dan XI IPA 6 SMA Negeri 4 Bandung. Penelitian ini dilakukan dalam dua tahap, yaitu tahap 1 berupa identifikasi learning obstacle dan tahap 2 berupa eksperimen pengujian pengaruh bahan ajar matematika berkarakter terhadap kemampuan pemecahan masalah dan disposisi matematika. Instrumen yang digunakan dalam penelitian ini adalah tes, angket disposisi, dan pedoman observasi. Learning obstacle yang teridentifikasi yaitu kemampuan siswa dalam mengidentifikasi masalah dan merancang model matematika, serta keterkaitan antar konsep matematika dan keterkaitan matematika dengan disiplin ilmu lain. Kesimpulan yang diambil dalam penelitian ini adalah model bahan ajar yang digunakan disesuaikan dengan learning obstacle siswa, peningkatan kemampuan pemecahan masalah matematis siswa yang pembelajarannya menggunakan bahan ajar matematika berkarakter lebih baik daripada siswa yang pembelajarannya menggunakan bahan ajar biasa, dan disposisi matematika siswa yang pembelajarannya menggunakan bahan ajar matematika berkarakter lebih baik daripada siswa yang pembelajarannya menggunakan bahan ajar biasa. Kata kunci: bahan ajar matematika berkarakter, pemecahan masalah matematis, disposisi matematik